2003
DOI: 10.1200/jco.2003.03.195
|View full text |Cite
|
Sign up to set email alerts
|

Three-Arm Randomized Study of Two Cisplatin-Based Regimens and Paclitaxel Plus Gemcitabine in Advanced Non–Small-Cell Lung Cancer: A Phase III Trial of the European Organization for Research and Treatment of Cancer Lung Cancer Group—EORTC 08975

Abstract: Conclusion: Gemcitabine plus cisplatin and paclitaxel plus gemcitabine do not increase overall survival in patients with advanced NSCLC as compared with paclitaxel plus cisplatin. Treatment was well tolerated, and most QoL parameters were similar, but costs associated with the nonplatinum arm were highest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
222
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 324 publications
(238 citation statements)
references
References 37 publications
7
222
0
4
Order By: Relevance
“…Reasons for exclusion were not stated in eight studies [30,31,40,42,43,48,57,64], whereas we were unable to assess if any exclusion criteria were applied in a trial published in Chinese only [46]. Response was assessed according to the World Health Organization standard criteria [72] in 19 trials [22,23,25,29,32,34,35,39,44,45,47,49,50,52,53,59,62,65,68], according to the Southwest Oncology Group guidelines [73] in two studies [21,24], and according to the Response Evaluation Criteria in Solid Tumors [74] in four trials [60,61,66,67].…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Reasons for exclusion were not stated in eight studies [30,31,40,42,43,48,57,64], whereas we were unable to assess if any exclusion criteria were applied in a trial published in Chinese only [46]. Response was assessed according to the World Health Organization standard criteria [72] in 19 trials [22,23,25,29,32,34,35,39,44,45,47,49,50,52,53,59,62,65,68], according to the Southwest Oncology Group guidelines [73] in two studies [21,24], and according to the Response Evaluation Criteria in Solid Tumors [74] in four trials [60,61,66,67].…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…In the study by Schiller et al [22] cisplatin-gemcitabine was compared with both cisplatin-paclitaxel and carboplatin-paclitaxel, and with cisplatin-vinorelbine; in the same way cisplatin-vinorelbine was compared with cisplatin-paclitaxel and with carboplatinpaclitaxel. The same approach was adopted when analyzing the studies by Fossella et al [24], Smit et al [25], Treat et al [43], Liu et al [57], and Ohe et al [66].…”
Section: Identification Of Trialsmentioning
confidence: 99%
See 2 more Smart Citations
“…This resulted in its use as a combination with platinum. Several clinical studies on new platinum-based doublets (Kelly et al, 2001;Schiller et al, 2002;Smit et al, 2003) produced similar results, but a meta-analysis suggested an absolute 1-year survival benefit of 3.9% for gemcitabinecisplatin chemotherapy when compared to other platinumcontaining regimens (Le Chevalier et al, 2005). Cisplatin is one of the most widely used platinum derivatives, however it is considered to link with significant toxicities, including severe nausea /vomiting, ototoxicity and neuropathy and renal toxicity, thus requiring adequate hydration.…”
Section: Discussionmentioning
confidence: 98%